Mutations in ATP6V1B1 and ATP6V0A4 genes cause recessive distal renal tubular acidosis in Mexican families. Issue 3 (14th February 2016) - Escobar, Laura I.; Simian, Christopher; Treard, Cyrielle; Hayek, Donia; Salvador, Carolina; Guerra, Norma; Matos, Mario; Medeiros, Mara; Enciso, Sandra; Camargo, María Dolores; Vargas‐Poussou, Rosa
Abstract: Background: Autosomal recessive distal renal tubular acidosis (dRTA) is a rare disease characterized by a hyperchloremic metabolic acidosis with normal anion gap, hypokalemia, hypercalciuria, hypocitraturia, nephrocalcinosis, and conserved glomerular filtration rate. In some cases, neurosensorial deafness is associated. dRTA is developed during the first months of life and the main manifestations are failure to thrive, vomiting, dehydration, and anorexia. Methods: Nine unrelated families were studied: seven children, a teenager, and an adult with dRTA. Hearing was preserved in four children. Coding regions of the genes responsible for recessive dRTA were analysed by Sanger sequencing. Results: Molecular defects were found in the genes ATP6V1B1 and ATP6V0A4 . We identified three homozygous variants in ATP6V1B : a frameshift mutation (p.Ile386Hisfs*56), a nucleotide substitution in exon 10 (p.Pro346Arg), and a new splicing mutation in intron 5. Three patients were homozygous for one novel (p.Arg743Trp) and one known (p.Asp411Tyr) missense mutations in the ATP6V0A4 gene. Three patients were compound heterozygous: one proband displayed two novel mutations, the frameshift mutation p.Val52Metfs*25, and a large deletion of exons 18–21; two probands showed the missense mutation p.Asp411Tyr and as a second mutation, p.Arg194Ter and c.1691+2dup, respectively. Conclusion: ATP6V0A4 and ATP6V1B1 genes were involved in recessive dRTA of Mexican families. All ATP6V1B1 mutations detected were homozygous and all patients developed sensorineural hearing loss (SNHL) early in infancy. ATP6V0A4 mutations were found in one infant and three children without SNHL, and in one teenager and one adult with SNHL confirming the phenotypic variability in this trait. The mutation p.Asp411Tyr detected in four Mexican families was due to a founder effect. Screening of these mutations could provide a rapid and valuable tool for diagnosis of dRTA in this population. Abstract : We identified the molecular defects in the genes ATP6V1B1 and ATP6V0A4 of nine nonconsanguineous Mexican families with dRTA.